Association between Dentin Hypersensitivity and Health/Oral Health-related Quality of Life: A Systematic Review and Meta-Analysis - Anna Rachel dos Santos Soares; Rayssa Soares Barbosa; Julya Ribeiro Campos; Loliza Luiz Figueiredo Houri Chalub; Allyson Nogueira Moreira; Raquel Conceição Ferreira (Association of Support to Oral Health Research (APESB), 2023)
Objective: To investigate the association between DH and Health (HRQoL) or Oral Health-Related Quality of Life (OHRQoL). Material and Methods: PubMed, Web of Science, Scopus, EMBASE, Cochrane, Scielo, LILACS/BBO, Biblioteca Digital de Teses e Dissertações (BDTD), Open Grey, and Google Scholar databases were screened in September 2019 (updated in October 2022). Observational studies were selected to compare HRQoL/OHRQoL(outcome) according to DH(exposure) or evaluate the association among these variables. Standardized Joanna Briggs Institute critical appraisal tool for analytical cross-sectional studies was used to analyze the risk of bias. A random-effects meta-analysis was conducted to synthesize evidence for the association between DH and OHRQoL. Results: 10 papers met inclusion criteria and were evaluated. In most studies, presenting or having a greater intensity of DH was associated with a negative impact on one's quality of life. However, most of these studies showed a moderate to high risk of methodological bias. The consistent finding from studies with a low risk of bias suggests a significant association between DH and OHRQoL. Meta-analysis was feasible for three studies with substantial heterogeneity. The pooled Odds Ratio was 2.14 (95%CI 1.15-3.99; I2=57,44%).Conclusion: Many studies presented a high risk of bias; therefore, the actual effect of DH on one's quality of life remains uncertain.